Prediction of Infiltration Capacities by Field Measurement and Selected Empirical Models for Irrigated Agriculture - , M. O. Alatise; , F. F. Akinola (Archives of Current Research International, 2017)
The study compared the infiltration capacities by field measurement and some empirical models for irrigation agriculture.The field measurement was carried out at the Farm Site of the Agricultural Engineering Department, Federal University of Technology, Akure. A double ring infiltrometer with inside diameter of 30 cm and outside diameter of 60 cm with height 67 cm was used to measure the infiltration rate at the experimental site. Three locations were selected at the site while three runs were carried out at each location. Soil samples were collected on different soil type at various sample points and at varying depths ranging from 10- 30 cm. The infiltration rates of water through the soil were measured. Thereafter, four infiltration equations namely Kostiakov, Horton, Green & Ampt and Philip adapted to ponded conditions were evaluated for their ability to predict infiltration into the predominant soil. The prediction of infiltration by the selected models shows fair to good agreement with the observed values. The overall performance rating shows the Kostiakov equation performing best, followed by Philip, Horton and Green and Ampt in that order. Also, four equations were obtained to predict the infiltration capacities from these models. From this study, it can be inferred that the evaluated parameters of the selected models can be used for obtaining the infiltration capacities of comparable soil types which are required for irrigated agriculture in other locations.